Effect of local strain energy to predict accurate phase diagram of III–V pseudobinary systems: case of Ga(As, Sb) and (In, Ga)As. (9th November 2020) - Han, Gyuseung; Yeu, In Won; Park, Jaehong; Ye, Kun Hee; Lee, Seung-Cheol; Hwang, Cheol Seong; Choi, Jung-Hae
Abstract: This work proposes an efficient and accurate methodology of ab initio thermodynamics to predict phase diagrams of III–V pseudobinary systems. The innumerable configurations of solid solutions are efficiently considered while maintaining accuracy by calculating the energies of freely relaxed configurations with the combined methodology using density functional theory calculations and cluster expansion. Then, the thermodynamic properties are calculated following a grand canonical ensemble framework that takes into account the local compositional fluctuation. The local strain energy induced by this local compositional fluctuation is found to be independent of the configuration; hence, it is calculated separately and added to the energy of a freely relaxed configuration, which significantly reduces the computational cost. This novel methodology is applied to calculate the phase diagrams of Ga(As, Sb) and (In, Ga)As, showing a good agreement with previous experimental reports. Notably, the strain energy is indispensable to predict phase diagrams accurately. It implies both the validity and the applicability of this method to other III–V pseudobinary systems. From an understanding of the crucial role of the strain energy in phase separation, an intuitive prediction is suggested through a simple estimation of the strain energy using the ratio of lattice parameters between various III–V semiconductor materials.